Managing bite risk for divers in the context of shark feeding ecotourism: A case study from French Polynesia (Eastern Pacific). (October 2018) - Clua, Eric E.G.
Abstract: Shark-based ecotourism has been recently expanding around the world. Provisioning sharks, however, is not without risk and accidental bites on humans are regularly reported. Such events may jeopardise the shark ecotourism industry and local economies. Through a case study from French Polynesia, I investigated whether changes in feeding practices of lemon sharks between the early 1990s and 2013 are related to recent accidental bites of divers. Hand-feeding, 'smelling' and surface feeding facilitated the development of agonistic behaviour in sharks, which resulted in accidental bites. The level of interaction between sharks and humans appears to be the most important driver for analysing bite-risk. This paper presents the very first framework for risk-analysis and will allow managers to better manage the risk associated with current practices in shark-feeding around the world. The paper also provides technical guidelines for the design of adequate legal frameworks that will support any sustainable shark feeding operation. Graphical abstract: Image 1 Highlights: Accidental bites linked to shark feeding can jeopardise this ecotourism industry. Bite risk seems positively correlated with specific feeding practices. The level of interactions between sharks and humans is a major driving factor. Based on this hypothesis, I propose a framework for accidental bite risk analysis. This tool should improve the management of shark-based ecotourism worldwide.